2020
DOI: 10.1186/s40959-020-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

A case report: high dose melphalan as a conditioning regimen for multiple myeloma induces sinus arrest

Abstract: High dose melphalan is commonly used as a conditioning regimen for autologous stem cell transplantation in multiple myeloma. There are reports of adverse cardiac events with melphalan manifested by supraventricular tachycardia and atrial fibrillation. Here, we report a rare case of a 58 year old female with multiple myeloma, who developed sinus arrest after autologous stem cell transplantation using high dose melphalan as a conditioning regimen. It was severe and rare, therefore, monitoring for cardiac toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…Cardinale et al showed that most commonly cardiotoxicity after anthracycline-containing therapy occurs within the first year and early treatment with angiotensin converting enzyme (ACE) inhibitors was crucial for a substantial recovery of cardiac function in this study [ 12 ]. Our results are in line with two recent publications, where LV ejection fraction improved after treatment with sacubitril/valsartan in patients treated with cardiotoxic cancer therapy [ 7 , 8 ]. However, in our present study we show that not only left ventricular but also the right ventricular function can be improved with sacubitril/valsartan in cancer-treated patients, a finding which was not examined in the previous registries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cardinale et al showed that most commonly cardiotoxicity after anthracycline-containing therapy occurs within the first year and early treatment with angiotensin converting enzyme (ACE) inhibitors was crucial for a substantial recovery of cardiac function in this study [ 12 ]. Our results are in line with two recent publications, where LV ejection fraction improved after treatment with sacubitril/valsartan in patients treated with cardiotoxic cancer therapy [ 7 , 8 ]. However, in our present study we show that not only left ventricular but also the right ventricular function can be improved with sacubitril/valsartan in cancer-treated patients, a finding which was not examined in the previous registries.…”
Section: Discussionsupporting
confidence: 93%
“…Until now, only few registries and small case reports have been published about sacubitril/valsartan in patients with cardiotoxicity induced cardiomyopathy [ 6 8 ]. The aim of the current study was to assess tolerability of sacubitril/valsartan in patients with a history of cancer in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…A common side effect of high-dose melphalan therapy is cardiotoxicity, which is manifested as supraventricular tachycardia and atrial fibrillation [ 92 , 93 ]. The use of a high concentration of melphalan in myeloablative therapy in preparation for hematopoietic cell transplantation is highly hepatotoxic, as it is associated with high enzyme growth rates and acute liver damage due to sinusoidal obstruction syndrome.…”
Section: “Weak Side” Of Melphalanmentioning
confidence: 99%